Influence of Brand Equity Dimensions on the Business Purchase Behavior of the Crispy Chicken Franchise in Tegal City - Sari Wiyanti; Niken Wahyu Cahyaningtyas (Institute of Computer Science (IOCS), 2022)
Crispy chicken in Indonesia becomes a competititve business and easy business to run. The risk of the crispy chicken franchise business is very low because the crispy chicken franchise brand is know to consumers. The franchisor built his brand equity, by developing a crispy chicken franchise. Franchise prefer to buy a crispy chicken franchise business that has high brand equity. The survey was toward 100 respondent and collected 75 questionnaires from crispy chicken traders in Tegal City. Data analysis techniques using multiple linear regression. The results can conclude that the dimensions of brand equity simultaneously affect business purchase behavior of the crispy chicken franchise in Tegal city.